PENGARUH METODE SCRAMBLE TERHADAP HASIL BELAJAR IPA SISWA KELAS IV DI GUGUS IV KECAMATAN MATARAM TAHUN PELAJARAN 2018/2019 - Sahara, Intan Dwi; Ratnadi, Ratnadi; Tahir, Muhamad; Hakim, Mansur (Jurnal Ilmiah Widya Pustaka Pendidikan, 2022)
This research aimed to know if there is a significance effect using scramble method   through   students'   learning  achievement   at  grade  IV  IPA  Cluster   IV Subdistrict Mataram Academic Year 2018/2019. This research used experimental qualitative  method  a  type  of Quasi  Experimental   Design  which  Nonequivalent Control Group Design.  The population of this research was all the students at grade forth in Cluster IV Subdistrict Mataram.  Probability  sampling was used to get the sample  in this  research  which  gain  class  IV  in  SDN  35 Mataram  and  SDN 44Mataram as the sample. The data collection technique in this research used learning implementation  observation sheets and cognitive learning achievement test which is pre-test  and post-test.  Data from the observation of learning implementation using the Scramble method were analyzed by using descriptive  analysis,  which are teaching and learning process  during the two meetings  could reach  100% (very good). The result of cognitive  learning  achievement  (pre-test  and post-test)  were analyzed by using covariance analysis, get the alpha score 0,029< 0,05 in experimental group and the score in the controlling group was 61,259 > 52,024 .   It showed that Ho is rejected and H alternative is accepted which stated there is significance effect using Scramble as a method  through  students'  learning  achievement  at grade  IV IPA Cluster  IV Subdistrict  Mataram  Academic  Year  2018/2019.  The use  of Scramble  method  in learning  process  can  affect  the  students'  learning  achievement,  and  it  is  being suggested to use it in teaching and learning process..